2016
DOI: 10.2224/sbp.2016.44.2.269
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parenting Behavior in Adolescents' Problematic Mobile Game Use

Abstract: With the rapid growth of smartphone use, problematic mobile game use among youth has become an increasingly salient social concern in South Korea. In this study, we empirically explored the relationship between parenting behavior and adolescents' problematic mobile game use. On the basis of the developmental perspective, we focused on students in 3 different age groups (N = 1,018: elementary school, n = 401; middle school: n = 333; high school, n = 284) and observed noticeable differences according to age gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Drawing on the literature review, we develop our research model to extrapolate several key determinants of intention to decrease use (Figure ). Problematic smartphone game use has emerged as a noteworthy concern that causes serious damages (Jang & Ryu, ). Studies have suggested that it can lead to health problems (Thomée et al, ), social anxiety (Lo et al, ), cognitive distortion (Li & Wang, ), poor academic performance (Leung & Lee, ) and many other serious consequences.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Drawing on the literature review, we develop our research model to extrapolate several key determinants of intention to decrease use (Figure ). Problematic smartphone game use has emerged as a noteworthy concern that causes serious damages (Jang & Ryu, ). Studies have suggested that it can lead to health problems (Thomée et al, ), social anxiety (Lo et al, ), cognitive distortion (Li & Wang, ), poor academic performance (Leung & Lee, ) and many other serious consequences.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Following the definition of problematic information technology (IT) use (Jang & Ryu, ; Lee & Cheung, ; Lopez‐Fernandez, Männikkö, Kääriäinen, Griffiths, & Kuss, ; Young & Rodgers, ), problematic smartphone game use denotes an impulse control disorder associated with dependent use of smartphone games, which causes negative consequences, such as social, work‐related and academic problems. It is characterized by uncontrolled acts with multiple negative consequences (Jang & Ryu, ). Widespread disturbing reports show that problematic use of smartphone games poses a significant threat to personal lives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with the expansion of Internet use at home and during leisure time in adolescents ( China Internet Network Information Center, 2016 ), a growing body of empirical research has examined the relationship between parental monitoring (along with other parental factors) and Internet gaming disorder. Recent studies have highlighted that low parental monitoring and poor parent–child relationship predicted higher levels of Internet gaming disorder in adolescents ( Liu et al, 2012 ; Koo and Kwon, 2014 ; Li et al, 2014 ; Bleakley et al, 2016 ; Jang and Ryu, 2016 ). However, the majority of research has focused on unidirectional effects of these two variables on Internet gaming disorder in adolescents; to our knowledge, no studies have yet examined the reciprocal relationships between parental monitoring, parent–child relationship, and Internet gaming disorder during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 57 studies conducted by Collier et al (2016) found that parental monitoring is associated with decreased gaming time and sexual behavior in adolescents. Furthermore, a survey of 1800 adolescents in South Korea revealed that parental monitoring might be effective in reducing problematic mobile game use ( Jang and Ryu, 2016 ). However, longitudinal data on how parental monitoring contributes to Internet gaming disorder in adolescents is inadequate.…”
Section: Introductionmentioning
confidence: 99%